2023
DOI: 10.1002/jgh3.12913
|View full text |Cite
|
Sign up to set email alerts
|

The influence of early adoption of nonenhanced computed tomography on management of patients with pyogenic liver abscess

Abstract: Background and Aim A pyogenic liver abscess (PLA) is an infectious disease with high in‐hospital mortality. It has no specific symptoms and is difficult to be diagnosed early in the emergency department. Ultrasound is commonly used to detect PLA lesions of PLA, but its sensitivity can be affected by lesion size, location, and clinician experience. Therefore, early diagnosis and prompt treatment (especially abscess drainage) are crucial for better patient outcomes and should be prioritized by clinical physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The pathogenic bacterium Klebsiella pneumoniae is commonly found in PLA patients with DM. 10 , 38 Zhang et al demonstrated that Klebsiella pneumoniae liver abscesses are mixed abscesses infected by Klebsiella pneumoniae along with other bacteria. 39 Guo et al reported that the relative abundance of Klebsiella in the pus cavity of PLA patients with DM was higher than that in PLA patients without DM.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic bacterium Klebsiella pneumoniae is commonly found in PLA patients with DM. 10 , 38 Zhang et al demonstrated that Klebsiella pneumoniae liver abscesses are mixed abscesses infected by Klebsiella pneumoniae along with other bacteria. 39 Guo et al reported that the relative abundance of Klebsiella in the pus cavity of PLA patients with DM was higher than that in PLA patients without DM.…”
Section: Discussionmentioning
confidence: 99%